Verbal brand identity from the teaching of design thinking, case Guayaquil city brand - Arias Villamar, John Alfredo (Scripta Mundi, 2023)
The present work is part of the teaching of Design thinking as a fundamental resource to solve problems of a communicational nature and related to the verbal identity of a brand. The aforementioned variables contribute in the significant development of sensory arguments interpretation, whether tangible or intangible. The objective of the research is to determine the importance of teaching Design thinking in processes of Guayaquil City brand development. Likewise, a group of 179 students of the fourth and sixth semester of the Graphic Design Career - FACSO - University of Guayaquil was selected, to expose it to challenges on the sensory content materialization whose dissemination scenario is digital media or social networks. The applied methodology is hermeneutics, since it is based on the interpretation of codes and symbols related to communication, giving rise to the tangible brand discourse configuration, in order to raise a sense of belonging in current users. The selected sample presented coherent results and within the real conditions of the selected user. The proposals are based on verbal brand identity criteria and indicators.